Fast-charging high-energy lithium-ion batteries via implantation of amorphous silicon nanolayer in edge-plane activated graphite anodes - Namhyung Kim (Nature Portfolio, 2017)
It is desirable to develop fast-charging batteries retaining high energy density. Here, the authors report a hybrid anode via incorporation of an implanted amorphous silicon nanolayer and edge-plane-activated graphite, which meets both criteria.